The Influence of the 5e Learning Cycle Model Based on Project Based Learning on Students' Critical Thinking Skills in Science Learning at Muhammadiyah 1 Elementary School - Hadrisah, Hadriah (LENTERNAL: Learning and Teaching Journal, 2025)
This study aims to design, implement, and determine the effect of the 5E Learning Cycle model based on Project-Based Learning (PjBL) on students' critical thinking skills in science learning at Muhammadiyah 1 Elementary School. The method used is quantitative with a quasi-experimental non-equivalent control group pretest-post-test design, involving two groups: an experimental group using the 5E Learning Cycle model based on PjBL and a control group using conventional learning methods. The research instruments include a HOTS-based critical thinking ability test, student activity observation sheets, and documentation. The results of data analysis showed that there was a significant difference between students' critical thinking skills in the experimental class and the control class. The experimental class experienced a significant increase based on the results of the Paired Sample t-test (t = -17.47, p